Surprise! Draw the scene: Visual recall reveals poor incidental working memory following visual search in natural scenes. - Cárdenas-Miller, Nicolás; O'Donnell, Ryan E.; Tam, Joyce; Wyble, Brad (Memory & Cognition, 2025)
Searching within natural scenes can induce incidental encoding of information about the scene and the target, particularly when the scene is complex or repeated. However, recent evidence from attribute amnesia (AA) suggests that in some situations, searchers can find a target without building a robust incidental memory of its task relevant features. Through drawing-based visual recall and an AA search task, we investigated whether search in natural scenes necessitates memory encoding. Participants repeatedly searched for and located an easily detected item in novel scenes for numerous trials before being unexpectedly prompted to draw either the entire scene (Experiment 1) or their search target (Experiment 2) directly after viewing the search image. Naïve raters assessed the similarity of the drawings to the original information. We found that surprise-trial drawings of the scene and search target were both poorly recognizable, but the same drawers produced highly recognizable drawings on the next trial when they had an expectation to draw the image. Experiment 3 further showed that the poor surprise trial memory could not merely be attributed to interference from the surprising event. Our findings suggest that even for searches done in natural scenes, it is possible to locate a target without creating a robust memory of either it or the scene it was in, even if attended to just a few seconds prior. This disconnection between attention and memory might reflect a fundamental property of cognitive computations designed to optimize task performance and minimize resource use.